Conservation for self-determination: Salween Peace Park as an Indigenous Karen conservation initiative. (June 2023) - Paul, Andrew; Roth, Robin; Sein Twa, Saw Paul
States have long used protected areas to consolidate control over Indigenous Peoples' territories, undermining community-based governance and access to resources. Despite this history, Indigenous Peoples around the world are increasingly designating their own protected areas to defend ancestral territories and assert self-determination. This paper examines Indigenous conservation politics in the Salween Peace Park in Kawthoolei, an autonomous territory of the Karen (Sino-Tibetan language-speaking peoples living primarily in Burma and along the Thai-Burma border). Local villagers and the Karen National Union envision the park as a grassroots initiative for peace in an area that has suffered decades of armed conflict between the Burmese military and the Karen movement for self-determination. Using the Salween Peace Park as a case study, we engage Indigenous scholarship on politics of recognition, resurgence, and refusal. We explore intersections and tensions between these political strategies, highlighting ways that Indigenous protected areas mobilize different forms of power to advance self-determination.